Methods and means of polarization-interference layer reconstruction and discrete phase scanning of jones matrix images of polycrystalline films of dehydrated bile - Ushenko, Yuriy; Soltys, Iryna; Harasym, Vasyl; Saleha, Oleksandr (Biophysical Bulletin, 2025)
Background: Modern methods of Mueller matrix polarimetry are aimed at determining the criteria and practical application of such markers in the differential diagnosis of pathological and necrotic changes in biological tissues of human organs. At the same time, little-studied and relevant are the issues related to matrix studies of another class of objects – dehydrated (dried) films of biological fluids (BF), the polycrystalline structure of which is associated with the composition and ratio of dissolved substances. Polarimetric analysis of the BF dehydrated film at the macroscopic level enables the retrieval of information about its molecular microstructure. In addition, BF are more easily accessible and do not require traumatic, sometimes dangerous, biopsy.Objectives: Development and experimental testing of the diagnostic efficiency of a new technique of polarization-interference reconstruction and layer-by-layer phase scanning of object fields of complex amplitudes with algorithmic reproduction of the real and imaginary components of Jones matrix images of polycrystalline films of dehydrated bile from healthy donors and patients with cholelithiasis.Materials and methods: Polarization interferometry, digital phase scanning and statistical analysis of algorithmically reproduced real and imaginary components of Jones matrix images of dehydrated bile films were used.Results: The results of the statistical analysis of the polarization-interference mapping method with digital Fourier reconstruction and phase scanning of complex amplitude distributions and algorithmic calculation of the real and imaginary components of Jones matrix images of bile film samples are presented and physically analyzed. Statistical markers that are most sensitive to changes in the polycrystalline structure of dehydrated bile films are established and high accuracy (97.6%) of differential diagnosis of cholelithiasis is demonstrated.Conclusions: General scenarios for the transformation of the statistical structure of the set of Jones matrix images, which are reproduced in different phase planes of the object field of dehydrated bile films, are established. A set of structures of self-assembled molecular networks (hereinafter referred to as supramolecular networks) formed during the dehydration of bile films, which are diagnostic markers most sensitive to pathological changes, has been identified. They turned out to be asymmetry and kurtosis, which characterize the coordinate distributions of the values of the real and imaginary components of the Jones matrix.